2019
DOI: 10.1098/rsif.2019.0148
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the start of a platelet aggregate by the shear rate and the cell-depleted layer

Abstract: Computer simulations were performed to study the transport of red blood cells and platelets in high shear flows, mimicking earlier published in vitro experiments in microfluidic devices with high affinity for platelet aggregate formation. The goal is to understand and predict where thrombus formation starts. Additionally, the need of cell-based modelling in these microfluidic devices is demonstrated by comparing our results with macroscopic models, wherein blood is modelled as a continuous fluid. Hemocell, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…HemoCell has been validated to reproduce the mechanical responses of an individual, healthy, RBC induced by sheared flow and optical tweezers, as well as accurately reproducing bulk flow hallmarks of whole blood such as the Fåhraeus-Lindqvist effect and the CFL [31]. With this validated RBC model HemoCell has been used to study the effects of RBC cytoplasmic viscosity contrasts in bulk flow [32], the role of hematocrit profiles on cell diffusivities in flow [33], as well as identifying the start of a platelet aggregate [40]. The capabilities of HemoCell allow the tracking of the individual suspended healthy RBCs, stiffened RBCs, and platelets that are present in the in vitro experiments reported in this study.…”
Section: Stiffened Red Blood Cell Numerical Modelmentioning
confidence: 99%
“…HemoCell has been validated to reproduce the mechanical responses of an individual, healthy, RBC induced by sheared flow and optical tweezers, as well as accurately reproducing bulk flow hallmarks of whole blood such as the Fåhraeus-Lindqvist effect and the CFL [31]. With this validated RBC model HemoCell has been used to study the effects of RBC cytoplasmic viscosity contrasts in bulk flow [32], the role of hematocrit profiles on cell diffusivities in flow [33], as well as identifying the start of a platelet aggregate [40]. The capabilities of HemoCell allow the tracking of the individual suspended healthy RBCs, stiffened RBCs, and platelets that are present in the in vitro experiments reported in this study.…”
Section: Stiffened Red Blood Cell Numerical Modelmentioning
confidence: 99%
“…The xy -component of the shear rate and stress were both derived from the flow field, because in this geometry the other components are negligibly smaller in comparison. The platelet count per second and platelet residence times were derived as described in [ 11 ]. The platelet count per second or platelet flux is the average number of platelets that were present on a certain location in the domain measured every 100 000 time steps divided by the total time of all time steps.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is difficult to obtain the exact values of shear rates and stresses in these devices. Previously, we found that shear rates are underestimated and shear stresses overestimated in continuum simulations assuming blood as a Newtonian fluid with a constant viscosity [ 11 ]. Since most researchers [ 4 , 5 , 12 , 13 ] used this assumption, there is a clear need to investigate the details of the flow domain and flow conditions in the microfluidic experiments in high-shear thrombosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The redistribution of RBCs and platelets in the case of disturbed flow (for example provided by vessel stenosis) was also suggested to influence the primary kinetics of platelet adhesion. 24 Continuous models describing platelet adhesion using the RBC-platelet interaction-induced flux of the platelet "substance" to the vessel wall or to the surface of platelet aggregates formed as a result of such a flux have been used to study the dynamics of occlusive thrombus formation in the stenosed arteries. 25 It is now clear that the first steps of platelet-dependent response are driven by purely mechanical processes of the interaction of platelet surface receptors (GPIbalpha and integrins) with their ligands on the surface of the injured vessel wall (von Willebrand factor [vWF], fibrinogen, fibronectin, laminins, etc.).…”
Section: In Silico Modeling Of Arterial Thrombus Formationmentioning
confidence: 99%